The Effect of External Pressure and Institutional Leadership on the Use of Local Government Performance Reports - Seralurin, Yohanes Cores; Patma, Kurniawan; Wijaya, Anthonius Ho Citra (Journal of International Conference Proceedings, 2023)
This research aims to provide empirical evidence on the effects of external pressure and institutional leadership on the utilization of local government performance reports. The hypothesis is built based on institutional theory, especially isomorphism pressure using coercive pressure shown in external pressure and Giddens' structuration theory using the concept of institutional leadership which is thought to influence the process of organizing performance measurement, namely the use of local government performance reports. Data collection and processing was carried out by conducting surveys by handing out questionnaires directly to all Papua Province government work units. The sample of respondents is state civil servants who have a role in preparing performance reports in each agency. The data analysis method uses Partial Least Square (PLS). The results, quite surprisingly, show that the external pressure variable has a significant negative effect on the use of local government performance reports and institutional leadership does not have a significant effect on the use of local government performance reports. The discussion will be reviewed in depth by paying attention to the latest conditions in Papua to try to understand the results of this research.